DETERMINAN KEPATUHAN WAJIB PAJAK USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN BANTUL: APAKAH ETIKA, PEMERIKSAAN, DAN DENDA BERPERAN? - Prasetyo , Agung; Hidayatulloh, Amir (KRISNA: Kumpulan Riset Akuntansi, 2022)
The purpose of this study is to analyze the factors that influence the compliance of MSME taxpayers. The population of this study is the taxpayers of Micro, Small and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta. The sample of this research is MSME taxpayers in Bantul Regency. The sampling technique used was purposive sampling, with the criteria for MSME actors who had a Taxpayer Identification Number. Respondents of this study amounted to 49 respondents. The data analysis of this research used multiple linear regression analysis, with the help of SPPS tool. This study obtained the results that MSME taxpayer compliance is influenced by ethics, audits, and tax penalties.